2007
DOI: 10.1677/jme-07-0054
|View full text |Cite
|
Sign up to set email alerts
|

The AMP-activated protein kinase activator, 5-aminoimidazole-4-carboxamide-1-b-d-ribonucleoside, regulates lactate production in rat Sertoli cells

Abstract: The aim of the present study was to investigate whether the AMP-activated protein kinase (AMPK), a key regulator of cellular energy homeostasis, is present in Sertoli cells and whether its activation by 5-aminoimidazole-4-carboxamide-1-b-Dribonucleoside (AICAR) results in the regulation of cell metabolism to ensure lactate supply for germ cell development. Sertoli cell cultures from 20-day-old rats were used. Western blot analysis for the a-subunit of AMPK showed that high levels of AMPK are present in Sertoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 48 publications
4
50
0
4
Order By: Relevance
“…Previous studies on rat and mice demonstrated the presence of AMPK in testis (Cheung et al 2000, Galardo et al 2007, Tartarin et al 2012b. In the chicken testis, both AMPKα, AMPKβ and the AMPKγ1 subunit were localised in the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies on rat and mice demonstrated the presence of AMPK in testis (Cheung et al 2000, Galardo et al 2007, Tartarin et al 2012b. In the chicken testis, both AMPKα, AMPKβ and the AMPKγ1 subunit were localised in the seminiferous tubules.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, activation of the AMPK pathway by another pharmacological drug (AICAR) in rat Sertoli cells stimulated lactate production (Galardo et al 2007). Under our conditions, the lactate production could be due to the role of metformin in inhibiting the respiratory chain complex 1, blocking mitochondrial activity (Leverve et al 2003) and promoting anaerobic respiration (Rena et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MCT4 plays a critical role in lactic acid efflux from skeletal muscle and is essential for muscle homeostasis. In rat primary sertoli cells, it has been reported that AICAR treatment increased MCT4 mRNA level and lactic acid production (Galardo et al 2007). However, the involvement of AMPK in MCT4 regulation in skeletal muscle is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…spermatogenèse, dans les cellules de Leydig 2 et dans les cellules de Sertoli 3 [19][20][21]. Dans les cellules de Sertoli, la voie de signalisation AMPK/mTOR (mammalian target of rapamycin) participe à la régulation de l'autophagie et de l'apoptose induite par des substances toxiques [24].…”
Section: Structure Et Expression De L'ampkunclassified